Science, technology and writing. the scientific framing of the written expression (2015)
A reflection on the role of writing in the development of scientific knowledge is made in order to show how science and technology fit a special writing. This descriptive study analyzed the formation of a written scientific language as a private discourse that wove its own terminology. This reflection highlights the ongoing construction of a special discourse genre in private places such as universities. A type of writing that carries a teleological distinction in contrast to other types, due to its accurate and objective requirements. Thus, the technoscientific legacy is contained mainly in a standardized writing that allows consultation and faster recoveries. The scientific articles and the research books are essential repositories of science and technology, documents like papers, reports and thesis form the so-called gray literature. The study concludes that science writing, for its specialty, specificity and purpose, is necessarily exclusive. The Science known by citizens comes through educational textbooks and scientific divulgation –mediating writings that transform technical terms to make science understandable to non-specialists